The Mid-Infrared Instrument for the James Webb Space Telescope, I: Introduction. (4th January 2016) - Rieke, G. H.; Wright, G. S.; Böker, T.; Bouwman, J.; Colina, L.; Glasse, Alistair; Gordon, K. D.; Greene, T. P.; Güdel, Manuel; Henning, Th.; Justtanont, K.; Lagage, P.-O.; et al.
Abstract: MIRI (the Mid-Infrared Instrument for the James Webb Space Telescope [ JWST ]) operates from 5 to 28.5 μm and combines over this range: (1) unprecedented sensitivity levels; (2) subarcsecond angular resolution; (3) freedom from atmospheric interference; (4) the inherent stability of observing in space; and (5) a suite of versatile capabilities including imaging, low- and medium-resolution spectroscopy (with an integral field unit), and coronagraphy. We illustrate the potential uses of this unique combination of capabilities with various science examples: (1) imaging exoplanets; (2) transit and eclipse spectroscopy of exoplanets; (3) probing the first stages of star and planet formation, including identifying bioactive molecules; (4) determining star formation rates and mass growth as galaxies are assembled; and (5) characterizing the youngest massive galaxies.